2021
DOI: 10.3390/d13010012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns in Macroherbivore Grazing in a Multi-Species Tropical Seagrass Meadow of the Great Barrier Reef

Abstract: Macroherbivory is an important process in seagrass meadows worldwide; however, the impact of macroherbivores on seagrasses in the Great Barrier Reef (GBR) has received little attention. We used exclusion cages and seagrass tethering assays to understand how the intensity of macroherbivory varies over space and time in the seagrass meadows around Green Island (Queensland), and what impact this has on overall meadow structure. Rates of macroherbivory were comparatively low, between 0.25–44% of daily seagrass pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…There are a multitude of seagrass grazers, from small invertebrates to megaherbivores (Valentine and Duffy, 2006). In the GBR, grazing by macro and mesoherbivores can influence seagrass canopy complexity, yet their impact can vary spatially and temporally (Scott et al, 2021a;Scott et al, 2021b). On a subtropical eelgrass meadow, five-weeks of exclusion showed that smaller grazers can lead to an increase in seagrass epiphytes, while exclusion of grazers such as small fish and shrimp led to increased seagrass cover, shoot height and density.…”
Section: Seagrass Grazersmentioning
confidence: 99%
“…There are a multitude of seagrass grazers, from small invertebrates to megaherbivores (Valentine and Duffy, 2006). In the GBR, grazing by macro and mesoherbivores can influence seagrass canopy complexity, yet their impact can vary spatially and temporally (Scott et al, 2021a;Scott et al, 2021b). On a subtropical eelgrass meadow, five-weeks of exclusion showed that smaller grazers can lead to an increase in seagrass epiphytes, while exclusion of grazers such as small fish and shrimp led to increased seagrass cover, shoot height and density.…”
Section: Seagrass Grazersmentioning
confidence: 99%
“…Recently, Calderon-Aguilera et al ( 2021) and Wabnitz et al (2010) placed marine turtles at the highest levels of the marine trophic webs they assessed, describing several positive and negative interspecific interactions of marine turtles with ecologically and economically important species. The latter supports the fact that marine turtles play a multifaceted role in ecosystem dynamics and functions, and their presence in turn has far-reaching effects on the viability of the ecosystems they inhabit, making them pertinent umbrella species (Eckert and Hemphill, 2005;Hannan et al, 2007;Rousso et al, 2015;Caŕdenas and Lew, 2016;Johnson et al, 2020;Mortimer et al, 2021;Scott et al, 2021;Wulf, 2021;Ashford et al, 2022;Guzmań-Hernańdez et al, 2022;Liceaga-Correa et al, 2022;Li et al, 2023).…”
mentioning
confidence: 78%
“…For example, a mass-balance model describing energy flow estimated low trophic overlap between T. m. manatus and other consumers (fishes and invertebrates) in an estuarine environment with limited seagrass abundance (Castelblanco-Martínez et al 2012). Similarly, in a protected region of the northern Great Barrier Reef with healthy seagrass ecosystems, the influence of macroherbivores on seagrass meadows was modest, suggesting low competition with D. dugon (Scott et al 2021b). However, Heck et al (2015) hypothesized that increasing numbers of T. m. latirostris could reduce forage biomass for juvenile fishes.…”
Section: Interactions With Competitorsmentioning
confidence: 99%